2017
DOI: 10.1182/blood-2017-05-786368
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of exhaustion in cured hep C

Abstract: In this issue of Blood, Del Padre et al 1 evaluated the impact of eliminating chronic antigen exposure on B-cell exhaustion in the human therapeutic setting of directacting antiviral therapy for chronic hepatitis C virus infection (HCV) complicated by mixed cryoglobulinemia (MC). The phenotype of hepatitis C-related MC B cells has been previously demonstrated by this group and others 2 to include low-level CD21 expression (CD21 low ) and hypoproliferation in response to stimulation either through the B-cell re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 10 publications
2
11
0
Order By: Relevance
“…In this study, we demonstrate an abnormal expansion of atypical B cells in CHB infection, which are defective in generating HBs specific antibody secreting cells. A similar expansion of tissue-like memory or atypical “exhausted” B cells is shown for other chronic infections including HIV, HCV and malaria 12 , 14 , 15 . Since chronic antigen exposure is a plausible factor behind their expansion, normalization of these cells is expected with effective virus control.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…In this study, we demonstrate an abnormal expansion of atypical B cells in CHB infection, which are defective in generating HBs specific antibody secreting cells. A similar expansion of tissue-like memory or atypical “exhausted” B cells is shown for other chronic infections including HIV, HCV and malaria 12 , 14 , 15 . Since chronic antigen exposure is a plausible factor behind their expansion, normalization of these cells is expected with effective virus control.…”
Section: Discussionsupporting
confidence: 54%
“…During chronic HIV infection, abnormal expansion of CD19+ CD10−CD20+ CD27−CD21− tissue like memory B cells expressing inhibitory receptor FcRL4 occurs, although this expansion is normalized with effective antiretroviral therapy 12 . Similar increase in these so called exhausted B cells occur during chronic hepatitis C infection 13 , cure of HCV using DAA therapy does not however normalize these expanded cells 14 (and our unpublished data). Plasmodium falciparum infection results in similar increase in these defective B cells with impaired B cell receptor signaling and responses 15 .…”
Section: Introductionmentioning
confidence: 55%
“…13 In addition, eltrombopag may be able to bypass the interferon γ-mediated blockade of TPO-R signaling, which is thought to be involved in the loss of stem cells in aplastic anemia. 16 Based on preclinical evidence, the proinflammatory cytokine interferon γ forms neutralizing heterodimers with endogenous TPO that block the extracellular binding site of the TPO-R; however, owing to its unique transmembrane binding site, eltrombopag can evade this blockage. 16 If supported by clinical data, these findings could explain why eltrombopag is effective in aplastic anemia, in which endogenous TPO levels are significantly elevated, but also have important clinical implications for other hematologic disorders involving chronic inflammation.…”
Section: Tpo-ras: Mechanisms Of Actionmentioning
confidence: 99%
“…16 Based on preclinical evidence, the proinflammatory cytokine interferon γ forms neutralizing heterodimers with endogenous TPO that block the extracellular binding site of the TPO-R; however, owing to its unique transmembrane binding site, eltrombopag can evade this blockage. 16 If supported by clinical data, these findings could explain why eltrombopag is effective in aplastic anemia, in which endogenous TPO levels are significantly elevated, but also have important clinical implications for other hematologic disorders involving chronic inflammation. 16,17 Independent of its TPO-RA activity, eltrombopag is also a strong iron chelator, able to decrease oxidative stress, and has shown antileukemic effects in preclinical studies.…”
Section: Tpo-ras: Mechanisms Of Actionmentioning
confidence: 99%
“…In a preclinical study, Vyxeos ® was demonstrated to selectively increase the exposure of daunorubicin and cytarabine in a fixed ratio in leukemia-laden bone marrow, thus resulting in a significantly prolonged effect with regard to leukemia suppression [40]. In clinical trials, it was shown to have superior efficacy and comparable toxicity to the standard combination of daunorubicin and cytarabine in patients with AML [41].…”
Section: Liposomal Drugs Approved For Use In Humansmentioning
confidence: 99%